Early-Onset Ovarian Cancer <30 Years: What Do We Know about Its Genetic Predisposition? - Horackova, Klara; Janatova, Marketa; Kleiblova, Petra; Kleibl, Zdenek; Soukupova, Jana (International journal of molecular sciences, 2023)
Ovarian cancer (OC) is one of the leading causes of cancer-related deaths in women. Most patients are diagnosed with advanced epithelial OC in their late 60s, and early-onset adult OC diagnosed ≤30 years is rare, accounting for less than 5% of all OC cases. The most significant risk factor for OC development are germline pathogenic/likely pathogenic variants (GPVs) in OC predisposition genes (including BRCA1, BRCA2, BRIP1, RAD51C, RAD51D, Lynch syndrome genes, or BRIP1), which contribute to the development of over 20% of all OC cases. GPVs in BRCA1/BRCA2 are the most prevalent. The presence of a GPV directs tailored cancer risk-reducing strategies for OC patients and their relatives. Identification of OC patients with GPVs can also have therapeutic consequences. Despite the general assumption that early cancer onset indicates higher involvement of hereditary cancer predisposition, the presence of GPVs in early-onset OC is rare (<10% of patients), and their heritability is uncertain. This review summarizes the current knowledge on the genetic predisposition to early-onset OC, with a special focus on epithelial OC, and suggests other alternative genetic factors (digenic, oligogenic, polygenic heritability, genetic mosaicism, imprinting, etc.) that may influence the development of early-onset OC in adult women lacking GPVs in known OC predisposition genes.
Keywords: genetická predispozice k nemoci; Genetic Predisposition to Disease; BRCA2 Protein; geny BRCA2; dospělí; lidé; protein BRCA2; nádory vaječníků; Germ-Line Mutation; BRCA1 Protein; Carcinoma, Ovarian Epithelial; protein BRCA1; genetic predisposition; Risk Factors; Ovarian Neoplasms; ženské pohlaví; germline pathogenic variant; Genes, BRCA2; Adult; early-onset; zárodečné mutace; rizikové faktory; ovarian cancer; Humans; epiteliální ovariální karcinom; Female